2012
DOI: 10.1007/s10571-012-9857-8
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic and Non-Synaptic Mitochondria in Hippocampus of Adult Rats Differ in Their Sensitivity to Hypothyroidism

Abstract: Hypothyroidism in humans provokes various neuropsychiatric disorders, movement, and cognitive abnormalities that may greatly depend on the mitochondrial energy metabolism. Brain cells contain at least two major populations of mitochondria that include the non-synaptic mitochondria, which originate from neuronal and glial cell bodies (CM), and the synaptic (SM) mitochondria, which primarily originate from the nerve terminals. Several parameters of oxidative stress and other parameters in SM and CM fractions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 68 publications
0
4
0
1
Order By: Relevance
“…Moreover, the observed effects were correlated with decreased free mitochondrial biogenesis in the CM of the cerebral cortex, and it is hypothesized that the impact of THs on free mitochondrial biogenesis could underlie their effects on respiration [ 85 ]. Interestingly, mitochondrial respiration changes in the abovementioned studies [ 83 , 84 , 85 ] were observed in CM but not in the synaptosomal mitochondrial fraction. Moreover, in CM mitochondria, the aerobic glycolysis process (measured as formation of lactate) was increased, which was connected with hexokinase—initial, rate-limiting enzyme of glycolysis located on the mitochondria outer membrane—activity enhancement.…”
Section: Role Of Thyroid Hormones In Brain Metabolism Regulation: Focus On Changes In Oxidative Phosphorylationmentioning
confidence: 82%
See 2 more Smart Citations
“…Moreover, the observed effects were correlated with decreased free mitochondrial biogenesis in the CM of the cerebral cortex, and it is hypothesized that the impact of THs on free mitochondrial biogenesis could underlie their effects on respiration [ 85 ]. Interestingly, mitochondrial respiration changes in the abovementioned studies [ 83 , 84 , 85 ] were observed in CM but not in the synaptosomal mitochondrial fraction. Moreover, in CM mitochondria, the aerobic glycolysis process (measured as formation of lactate) was increased, which was connected with hexokinase—initial, rate-limiting enzyme of glycolysis located on the mitochondria outer membrane—activity enhancement.…”
Section: Role Of Thyroid Hormones In Brain Metabolism Regulation: Focus On Changes In Oxidative Phosphorylationmentioning
confidence: 82%
“…Currently, research increasingly differentiates the function of mitochondria depending on their location in nervous tissue and distinguishes two major populations of mitochondria: those derived from neuronal and glial cell bodies (CM) and synaptic mitochondria (SM) versus those derived from nerve terminals. Zhuravliova et al [ 83 ] demonstrated elevated redox level of copper of cytochrome oxidase and increased production of peroxides in the presence of substrates of complex I (glutamate and malate) in the CM of hippocampi of hypothyroid (methimazole-treated) rats, whereas succinate-induced H 2 O 2 release was diminished. Furthermore, previous data [ 84 , 85 ] showed that in the CM of hypothyroid neonates, there was diminished activity of complex I and reduced transmembrane potential, rate of oxidative phosphorylation and oxygen consumption.…”
Section: Role Of Thyroid Hormones In Brain Metabolism Regulation: Focus On Changes In Oxidative Phosphorylationmentioning
confidence: 99%
See 1 more Smart Citation
“…Полученные данные позволяют чётко дифференцировать две фракции митохондрий: в телах нейрональных, глиальных клеток и в синапсах. По данным E. Zhuravliova и соавт., при гипотиреозе в митохондриях нейронов и глии усиливался аэробный гликолиз, связанный с активностью гексокиназы, при этом адаптивная активация распада глюкозы в синаптических митохондриях не наблюдалась [32]. Т3 может противодействовать неблагоприятным изменениям, наблюдаемым в митохондриях нейронов головного мозга при гипотиреозе, путём нормализации дыхательных процессов и регуляции транскрипции митохондриальных генов (ND4, 12S рРНК, 16S рРНК и Cox III) [33].…”
Section: влияние йодтиронинов на окислительный стресс при острой ишем...unclassified
“…There are roughly two sources of mitochondria in the brain. One is called non-synaptic mitochondria, mainly from neurons and glial cell bodies, and the other is called synaptic mitochondria, mainly from nerve terminals [ 35 ]. Using two-dimensional differential gel electrophoresis and mass spectrometry to detect synaptic proteins, the data show significant differences in superoxide dismutase [Mn] (Sod2) and complement component 1Q subcomponent binding protein (C1qbp), which supports the idea that synapses are highly sensitive to oxidative stress[ 36 ].…”
Section: Mitochondrial Function In the Physiological And Pathological...mentioning
confidence: 99%